Efficient End-to-End Secure Key Management Protocol for Internet of Things - Yamina Benslimane; Khelifa BenAhmed (Institute of Advanced Engineering and Science, 2017)
Internet of things (IoT) has described a futurevision of internetwhere users, computing system, and everyday objects possessing sensing and actuating capabilities are part of distributed applications and required to support standard internet communication with more powerful device or internet hosts. This vision necessitates the security mechanisms for end-to-end communication. A key management protocol is critical to ensuring the secure exchange of data between interconnecting entities, but due to the nature of this communication system where a high resource constrained node may be communicating with node with high energy makes the application of existing key management protocols impossible. In this paper, we propose a new lightweight key management protocol that allows the constrained node in 6loWPAN network to transmit captured data to internet host in secure channel. This protocol is based on cooperation of selected 6loWPAN routers to participate in computation of highly consuming cryptographic primitives. Our protocol is assessed with AVISPA tool, the results show that our scheme ensured security properties.